25.8k views
4 votes
Please help me with this question ​

Please help me with this question ​-example-1
User Eozgonul
by
4.3k points

2 Answers

4 votes

Answer:

NEGATIVE 29

Explanation:

p

Exponents

Multiply

D

Add

Subtract

So the first exponent is


2^(2) which is 4

So now we have multiply so

4 x ( - 4 + - 3 )

4 x - 4 = - 16

4 x - 3 = - 12

So our new equation is

- 12 - 16 - 1 = - 29 :)

So the answer is NEGATIVE 29

User Ilyssis
by
5.0k points
5 votes

Answer:

-29

Explanation:

(−4−3)(2^2)−1

=−7(2^2)−1

=(−7)(4)−1

=−28−1

=−29

User Kapitan
by
4.7k points